Association of Early Drain Removal with Formation of Seroma in Breast Cancer Patients After Modified Radical Mastectomy - Ramadanus; Daan Khambri; Wirsma Arif Harahap (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The installation of drainage after MRM surgery has been aimed at reducing seroma formation. However, when the drain should be removed has not been studied well. This study aims to determine the association of early drain removal with seroma formation. Methods: A nested cohort study was conducted on 40 breast cancer patients undergoing MRM surgery. Patients were divided into 2 groups; off-drain day I and day III post-surgery. Seroma formation was assessed 7 days after the patient was discharged. Results: Seroma formation seven days after discharge occurs in 25 of the total 40 patients (62.5%). There was no difference in seroma incidence between groups of patients on the off-drain day I and day III seven days after discharge (65% vs. 60%) (p 1,000) or the number of seromas (157.31 +120.00 ml vs. 149.58 + 110.00 ml) (p 0.437). Conclusion: Removing the drain faster does not reduce the incidence and number of seromas seven days after discharge.